Electrically conducting diamond films grown on platinum foil for neural stimulation - Sikder, Kabir; Shivdasani, Mohit; Fallon, James; Seligman, Peter; Ganesan, Kumaravelu; Villalobos, Joel; Prawer, Steven; Garrett, David (IOP Publishing, 2019)
Objective With the strong drive towards miniaturization of active implantable medical devices and the need to improve the resolution of neural stimulation arrays, there is keen interest in the manufacture of small electrodes capable of safe, continuous stimulation. Traditional materials such as platinum do not possess the necessary electrochemical properties to stimulate neurons safely when electrodes are very small (i.e. typically less than about 300 um (78400 microm2)). While there are several commercially viable alternative electrode materials such as titanium nitride and iridium oxide, an attractive approach is modification of existing Pt arrays via a high electrochemical capacitance material coating. Such a composite electrode could still take advantage of the wide range of fabrication techniques used to make platinum-based devices. The coating, however, must be biocompatible, exhibit good adhesion and ideally be long lasting when implanted in the body. Approach Platinum foils were roughened to various degrees with regular arrays of laser milled pits. Conducting diamond films were grown on the foils by microwave plasma chemical vapor deposition. The adhesion strength of the films to the platinum was assessed by prolonged sonication and accelerated aging. Electrochemical properties were evaluated and compared to previous work. Main results In line with previous results, diamond coatings increased the charge injection capacity of the platinum foil by more than 300% after functionalization within an oxygen plasma. Roughening of the underlying platinum substrate by laser milling was required to generate strong adhesion between the diamond and the Pt foil. Electrical stress testing, near the limits of safe operation, showed that the diamond films were more electrochemically stable than platinum controls. Significance The article describes a new method to protect platinum electrodes from degradation in vivo. A 300% increase in charge injection means that device designers can safely employ diamond coated platinum stimulation electrodes at much smaller sizes and greater density than is possible for platinum. .
Keywords: Diamond; Electrode; Neural Stimulation; Medical implant; Capacitance; Coating; Platinum